Formulation and Physical Evaluation of Cream Containing Neem Oil 5% - Patihul Husni; Anggia Diani Amalia; Soraya Ratnawulan Mita; Norisca Aliza Putriana (Indonesian Journal of Pharmaceutics, 2019)
Permethrin Cream 5%, a topical scabicidal agent, is usually used for the treatment of infestation with Sarcoptes scabiei (scabies). Nowadays, neem oil,  a vegetable oil pressed from the fruits and seeds of the neem (Azadirachta indica A.Juss), is reported having an antiscabies effect. The aim of the study was to formulate and evaluate the physical properties of cream containing neem oil 5%. Methods of the study were characterization of physicochemical properties of neem oil, preparation and physical stability study at room temperature (25 oC) and 40 oC for three months storage of the neem oil 5% cream. Physical evaluation involved organoleptic, homogeneity, pH, tipe of cream and  viscosity. The study results showed that all of the physicochemical properties of neem oil met the requirement. The cream were white to yellowish white, characteristic neem oil odor, homogenous cream, pH ± 8, viscosity approximately 2000-8000 cps and o/w cream. Three months storage of the cream showed that the formula resulted a stable cream physically.Keywords: neem oil, permethrin, scabies, Azadirachta indica A.Juss